Pengujian Perda dan Perdes Pasca Perubahan UU Pemda dan UU Desa - Enrico Simanjuntak (The Constitutional Court of the Republic of Indonesia, 2016)
The development of contemporary public law (both in the field of constitutional law and administrative law) in Indonesia was marked by the strengthening of the internal settlement administration assertion as a means of testing the legal norms of both abstract and concrete. With variations, in a legal dispute concerning the norms of concrete, these developments containing fragmentation models for partly governs how the advanced mechanism in the judiciary after taken administrative effort (eg, Law Administration) and some not at all set up (eg, Law Reform State Civil). Some of the latest legislation select general-abstract norm testing internally without linking them with the possibility of testing judicially by the judiciary, among others: Law on Local Government and Law Village. In both the legislation does not regulate how the mechanism of local regulation (Perda) or village laws (Perdes) canceled by the governor or regent / mayor, whether they can be tested back to the judiciary through judicial review mechanism. This paper intends to discuss how the implementation of the authority of judicial review by Supreme Court after the enactment Law of Local Goverment or Law of Village which is not regulated by the latest legal mechanism to test regional law in the form of regulation (local laws), including Perdes (Village Laws), whereas previous products or similar laws regulate otherwise.